London 2012 Olympic and Paralympic Games: public health surveillance and epidemiology. - McCloskey, B.; Endericks, T.; Catchpole, M.; Zambon, M.; McLauchlin, J.; Shetty, N.; Rohini, M.; Turbitt, D.; Smith, G.; Crook, P.; Severi, E.; Jones, J.; et al. (The Lancet, 2014)
Mass gatherings are regarded as potential risks for transmission of infectious diseases, and might compromise the health system of countries in which they are hosted. The evidence for increased transmission of infectious diseases at international sporting mass gatherings that attract many visitors from all over the world is not clear, and the evidence base for public health surveillance, epidemiology, and response at events such as the Olympics is small. However, infectious diseases are a recognised risk, and public health planning is, and should remain, a crucial part of the overall planning of sporting events. In this Series paper, we set out the planning and the surveillance systems that were used to monitor public health risks during the London 2012 Olympic and Paralympic Games in the summer of 2012, and draw attention to the public health issues -infectious diseases and chemical, radiation, and environmental hazards - that arose. Although the absolute risk of health-protection problems, including infectious diseases, at sporting mass gatherings is small, the need for reassurance of the absence of problems is higher than has previously been considered; this could challenge conventional public health surveillance systems. Recognition of the limitations of health-surveillance systems needs to be part of the planning for future sporting events.